ANALISIS KELAYAKAN FINANSIAL USAHA TERNAK BABI (Studi Kasus : Peternak Babi Desa Kalasey Satu Kecamatan Mandolang Kabupaten Minahasa) - Winokan, Anita Meilina; Tilaar, Wenny; Kalangi, Jolanda Kitsia Juliana (Sam Ratulangi University, 2022)
This study aims to determine the level of profit and analyze the financial feasibility of pig farming. The research was conducted using a case study method on pig farmers in Kalasey Satu Village, Mandolang District, Minahasa Regency from May 2021 to July 2021. The selection of respondents was carried out by purposive sampling. The data used are primary data and secondary data. Primary data were obtained from respondents through direct interviews with one pig farmer respondent. Secondary data were obtained from various sources, namely the Village Office, the Central Statistics Agency (BPS) and the Minahasa Regency Agriculture Office. The results showed that with an investment of Rp 62.035.000,00, and the production cost is Rp 1.028.555.563,00 the proceeds from the sale of pigs amounted to Rp 1,227,440,000,00 and a profit of Rp 136,849,437,00. The results of the analysis show the value of Net Present Value (NPV) = 36.010.033, Net Benefit Cost Ratio (Net B//C) = 1.51, Internal Rate of Return (IRR) = 29.79%, Payback Period (PP) = 1.48. Based on the results of the financial feasibility analysis, the pig farming business in Kalasey Satu Village earns a profitable income and is feasible to continue.